2013
DOI: 10.1016/j.ophtha.2012.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma Severity and Medication Adherence in a County Hospital Population

Abstract: Objective To assess the association between disease severity and adherence with glaucoma medications in a county hospital population. Design Cross-sectional study. Participants One hundred and twenty-six patients diagnosed with glaucoma receiving intraocular pressure (IOP) lowering medication were recruited from the San Francisco General Hospital Ophthalmology Clinic. Methods Subjects completed an oral questionnaire to assess demographic information, knowledge of glaucoma, and perceptions of glaucoma med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 35 publications
2
24
0
4
Order By: Relevance
“…9 A negative association between visual field defect severity and adherence, observed in a crosssectional study, 10 may be more related to disease progression and outcomes following nonadherence as opposed with baseline severity (cross-sectional design cannot provide definite information about cause-and-effect relationship). Our finding of a positive association between baseline IOP and the following adherence may suggest a psychological effect.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…9 A negative association between visual field defect severity and adherence, observed in a crosssectional study, 10 may be more related to disease progression and outcomes following nonadherence as opposed with baseline severity (cross-sectional design cannot provide definite information about cause-and-effect relationship). Our finding of a positive association between baseline IOP and the following adherence may suggest a psychological effect.…”
Section: Discussionmentioning
confidence: 97%
“…[4][5][6] There is substantial evidence suggesting that low adherence with topical and systemic glaucoma treatment is common 6,7 and associated with progression of visual field loss, high rate of glaucoma surgeries, and blindness. [8][9][10] Many papers suggested that nonadherence to chronic treatment may be a major barrier to controlling chronic health conditions, particularly asymptomatic diseases, 11 and glaucoma that requires lifelong and frequent follow-up care and daily treatment is of no exception. Elevated IOP and glaucomatous damage are usually asymptomatic up to a severe damage and advanced disease.…”
mentioning
confidence: 99%
“…If patients do not believe that glaucoma will affect them because they have not noticed any change in their vision, do not have a good, trusting relationship with their eye care provider, do not understand the chronic nature of glaucoma, do not have a good support system at home, or cannot afford management and treatment for their glaucoma, it is very likely that patients with any of these important barriers will be poorly adherent to their treatment regimen. Poor adherence to glaucoma medications and follow-up visits is associated with more advanced glaucomatous disease 17,18,2022 .…”
Section: Discussionmentioning
confidence: 99%
“…Poor adherence to medications is a multifactorial issue, and previous studies have identified many barriers to glaucoma medication adherence including cost 58 ; forgetfulness 5,6,810 ; side effects 6,8,10,11 ; difficulty instilling eye drops 5,6,811 ; skepticism that glaucoma will cause vision loss 5,9,12 ; skepticism that glaucoma medications are effective 5,9,11,12 ; a lack of knowledge about glaucoma 5,6,9,13 ; a lack of self-efficacy 9,14 ; difficulties with the medication schedule 6,8,10 ; a poor doctor patient relationship 15 ; and perceived life stress 16 . Ung and colleagues found that those with less severe disease were less adherent to their medications 17 , while those with more severe disease were less adherent with their follow-up care 18 , indicating that there may be different issues that face glaucoma patients early and later in their disease process.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, 1 study found an association between medication adherence and worsening disease severity. 6 These studies suggest that such individuals may actually be at greater risk of substantial disease worsening and severe vision loss than those patients who sometimes miss their medications but who see their ophthalmologist at appropriate intervals.…”
mentioning
confidence: 99%